Women’s Quality-of-Life Trajectories During Pregnancy and Postpartum Periods by Mode of Birth: A Prospective Cohort Study - Alayna Carrandi; Yanan Hu; Maria Forslund; Jenny Gamble; Debra Creedy; Emily Callander; Valerie Slavin (Maternal and Child Health Journal, 2026)
Abstract Objectives To determine the quality-of-life scores of women during pregnancy and postpartum and compare the differences by mode of birth. Methods A secondary analysis of a prospective, observational cohort study comprising 2866 pregnant women in Queensland, Australia. Women’s quality-of-life scores were collected at 36 weeks of gestation and 6- and 12-week postpartum and converted into utility values. Results On average, quality-of-life utility scores increased from 36 weeks of gestation to 12 weeks postpartum, regardless of birth type. After adjusting for socioeconomic characteristics, women who went on to have a planned caesarean section had a significantly lower utility score at 36 weeks of gestation compared to women who went on to have a spontaneous vaginal birth (adjusted mean difference = − 0.07; 95% CI − 0.11, − 0.02); women who did not have select birth type had a statistically significantly lower utility score at 36 weeks of gestation compared to women who had a select birth type (adjusted mean difference = − 0.05; 95% CI − 0.08, − 0.02). No significant differences were observed for other birth types at 6- and 12-week postpartum. Conclusions for Practice Women’s quality of life improves from late pregnancy to postpartum. Further research is needed to develop targeted interventions to improve quality of life among women at higher risk of low quality of life and adverse pregnancy and birth outcomes, however we did not identify any differences by mode of birth.